Learning City-Regions Revisited: A New Way Forward - Wilson, Bruce (The journal of contemporary issues in business and government, 2014)
Research and policy linking learning with place has been used widely over the past two decades to describe strategies which enable communities, cities and regions to reinvent themselves in the wake of industrial or other decline. When faced with significant economic and social challenges, this has been a way of encouraging stakeholders to rethink the resources and opportunities available to invigorate the local economy and, in particular, to promote employment growth. ‘Learning’ has been recognised as a critical element of the processes through which key organisations and people invent new responses to the local challenges. However, after a decade or so of great activity, use of the concept of the learning ‘place’ (city- region, as it is identified here) has become less common, and theoretical critique of the concept has become stronger. Yet it is readily apparent that the fundamental interest in knowledge and its application in place continues apace, such that we now find literature engaged with ‘knowledge cities’ and ‘smart’ cities coming to the fore. This paper reviews the ‘learning city-region’ concept, and the implications of current debates. While the conceptualisation has been problematic, it continues to offer important insights into the ways in which economic development depends on knowledge and learning, well beyond a narrowly construed individual skills formation agenda.